Review on the Encapsulation, Microencapsulation, and Nano- Encapsulation: Synthesis and Applications in the Process Industry for Corrosion Inhibition - Gujar, Jotiram; Patil, Sanjay; Sonawane, Shriram (Current Nanoscience, 2024)
Background: Surfaces of materials often corrode and deteriorate due to environmental conditions. There are various widely used methods of reducing corrosion rates to increase the lifetime of materials and equipment. Recently, there has been a growth in the use of nanotechnology to protect metals against corrosion. The application of nano-encapsulation techniques in the process industry is one of the important eras of nanotechnology. This review paper focuses on encapsulation, microencapsulation, and nano-encapsulation methods, emphasizing nanoencapsulation applications as corrosion inhibitions in the process industry.Methods: Materials based on the self-healing mechanism were used in advanced applications such as structures, batteries, and coatings. These technologies may be studied in two ways: compounds with intrinsic self-healing properties and extrinsic self-healing materials with additives such as microcapsules filled with healing agents. Nano-coatings have advantages, like accelerated ground hardness, adhesive energy, long-time period and/or high-temperature corrosion resistance, tribological residence enhancement, etc. Nano-coatings can also be carried out in thinner and smoother layers, considering flexibility, accelerated performance, decreased fuel costs, and smaller carbon footprints, as well as occasional maintenance. The review of corrosion characteristics of polymeric nanocomposite material was discussed in this paper.Results: This review paper presents an updated overview summarizing the latest advances in the various micro/nanocarriers used for self-healing corrosion protective coatings.Conclusion: With this information, the investigators will be able to modify the structure of the inhibitor to get the necessary corrosion inhibition capabilities. The need for a physical examination is rising as a result.
Keywords: nanotechnology